Scaffold Implant Into the Epididymal Adipose Tissue Protects Mice From High Fat Diet Induced Ectopic Lipid Accumulation and Hyperinsulinemia - Hendley, Michael A.; Isely, Christopher; Murphy, Kendall P.; Hall, Hayley E.; Annamalai, Prakasam; Gower, R. Michael (Frontiers in Bioengineering and Biotechnology, 2020)
Ectopic lipid accumulation, the deposition of lipids in lean tissue, is linked to type 2 diabetes through an association with insulin resistance. It occurs when adipose tissue fails to meet lipid storage needs and there is lipid spillover into tissues not equipped to store them. Ectopic lipid contributes to organ dysfunction because lipids can interfere with insulin signaling and other signaling pathways. Clinical studies indicate that decreasing ectopic lipids through diet and exercise is effective in treating type 2 diabetes; however, its prevalence continues to rise. We propose that strategies to improve lipid handling in the adipose tissue would be adjunctive to healthy lifestyle modification and may address difficulties in treating type 2 diabetes and other syndromes spurred by ectopic lipid. Herein, we investigate biomaterial implants as a means to increase lipid utilization in adipose tissue through the recruitment of highly metabolic cells. Poly(lactide-co-glycolide) scaffolds were implanted into the epididymal fat of mice fed a high fat diet that overwhelms the adipose tissue and promotes ectopic lipid accumulation. Over 5 weeks, mice with scaffolds gained less weight compared to mice without scaffolds and were protected from hyperinsulinemia. These effects correlated with a 53% decrease in triglyceride in the gastrocnemius and a 25% decrease in the liver. Scaffolds increased CPT1A protein levels in the epididymal fat and histology revealed high expression of CTP1A in the cells infiltrating the scaffold relative to the rest of the fat pad. In addition, lacing the scaffold with resveratrol increased CPT1A expression in the epididymal fat over scaffolds with no drug; however, this did not result in further decreases in weight gain or ectopic lipid. Mechanistically, we propose that the cellular activity caused by scaffold implant mitigates the lipid load imposed by the high fat diet and leads to a substantial decrease in lipid accumulation in the muscle and liver. In conclusion, this study establishes that a tissue engineering approach to modulate lipid utilization in the epididymal fat tissue can mitigate ectopic lipid accumulation in mice fed a high fat diet with positive effects on weight gain and whole-body insulin resistance.